2014
DOI: 10.1007/s11916-014-0412-9
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Neuromodulation: A Review

Abstract: Peripheral nerve stimulation (PNS) is likely the most diverse and rapidly expanding area of neuromodulation. Its expansion has become possible due to both technological and clinical advances in pain medicine. The first implantable systems were surgically placed. However, it is currently commonplace to use percutaneous leads, as this approach has become instrumental in its expansion. The first percutaneous peripheral nerve stimulators were reported in 1999. Cylindrical leads were implanted to stimulate the grea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 96 publications
0
43
0
2
Order By: Relevance
“…6 Moreover, high-frequency TENS affects the δ-opioid receptor and increases the levels of β-endorphins in the bloodstream and enkephalin in the cerebrospinal fluid. 10,27 With the possible exception of endogenous opiate release, the 'gate control theory' is in fact the most M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 14 tenable view. 2,12,16,21 This was advanced in 1965 by Melzack and Wall, who found that activation of non-noxious afferent Aβ fibers may inhibit the Aδ and C fibers that mediate nociceptive transmission.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Moreover, high-frequency TENS affects the δ-opioid receptor and increases the levels of β-endorphins in the bloodstream and enkephalin in the cerebrospinal fluid. 10,27 With the possible exception of endogenous opiate release, the 'gate control theory' is in fact the most M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 14 tenable view. 2,12,16,21 This was advanced in 1965 by Melzack and Wall, who found that activation of non-noxious afferent Aβ fibers may inhibit the Aδ and C fibers that mediate nociceptive transmission.…”
Section: Discussionmentioning
confidence: 99%
“…However, no randomized controlled trial has yet been performed. 10,27 Hence, the principal aim of this study was to evaluate the efficacy and tolerability of tONS (compared with TPM) in migraine patients and to explore whether different tONS frequencies influenced treatment effectiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of neuralgia symptoms may have been purely coincidental, but a possible explanation for the patient's neuralgia is perineural invasion of the ACC affecting the V 1 and V 2 branches of the trigeminal nerve, with these nerve branches stimulated by application of the TENS unit resulting in the patient's new symptoms. Typically, direct electrical stimulation of peripheral nerves causes decreased excitability, resulting in pain reduction, 17 and the authors speculate that the patient had a paradoxical response to the TENS therapy. The patient's complaint of persistent right otalgia, which had been previously evaluated by multiple health care Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromodulation is a diverse and rapidly expanding field of medicine that may prove to be revolutionary in the treatment of neuropathic CP 64, 65 . The modern era of neuromodulation in CP relief began in 1967 when Gol reported that repeated intracranial stimulation of the septal area resulted in effective pain control in several patients with cancer 66 .…”
Section: Non-pharmacological Treatmentsmentioning
confidence: 99%